A study of renal and gonadal vein variations - Vijisha Phalgunan; N Mugunthan; Devi Jansi Rani; J Anbalagan (Wolters Kluwer Medknow Publications, 2012)
Background and aims: The development of the renal veins is a complex process with many possible alternative patterns of fomation.Variations of renal veins are usually clinically silent until discovered during venography, operation or autopsy. In the era of renal transplantation , a meticulous knowledge of anatomy and variational patterns of renal vein is mandatory. The present study is aimed at finding out the incidence of variations in the drainage pattern of renal vein and gonadal vein and to correlate its clinical and embryological significance. Materials and methods: Twenty cadavers (twelve males and eight females) of adult age procured from Mahatma Gandhi Medical College and Research Institute, Puducherry were included in the study. Renal and gonadal veins on both sides were dissected and the pattern of termination of the renal and gonadal veins were observed and studied on both sides. Results: Out of twenty cadavers, two male cadavers showed the presence of termination of right testicular vein into right renal vein and both right kidneys showed multiple right renal veins. In the remaining 18 cadavers both renal and gonadal veins terminated in normal pattern. Conclusion: In present study 10% incidence of variation of right testicular vein draining into right renal vein was found, with the associated presence of multiple renal veins. The knowledge of these variations would be of definite help to renal transplant surgeons and clinicians.